(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Treatment of soft tissue defects in the fingers requires the preservation of functional integrity while maintaining aesthetic outcomes. Various methods exist for treating these injuries, among which the cross-finger flap has proven to be a reliable technique due to its procedural simplicity and lack of requirement for microsurgical expertise. However, for defects where a length discrepancy exists between digits - typically between the thumb and the index finger - flap selection and design remain a significant challenge and concern for surgeons. To address this issue, we utilized a cross-finger flap designed in a "flag" configuration harvested from the dorsum of the adjacent finger. Objectives: To evaluate the initial results of covering finger soft tissue defects using the cross-finger flag flap, while discussing the advantages and limitations of the technique. Methods: A descriptive case series of 11 clinical cases presenting with soft tissue defects exposing tendons or bones of the fingers underwent reconstruction with a cross-finger flag flap at Van Phuc 2 General Hospital. Results: The total flap survival rate was 100% . The size of the soft tissue defects ranged from 1x1 cm to 3.5x1.5 cm. Conclusion: The cross-finger flag flap yields favorable outcomes in the treatment of finger soft tissue defects, particularly for thumb defects where a length discrepancy exists between the donor and recipient sites.